Development of Modeling Forage Crop Irrigation Using Fao– Aqua Crop 2012 Program, Salamiyya, Syria - Yaghi, Tammam; Awadis, Arslan; Boshra, Khozam; Muna, Yaghi (New Countryside, 2025)
To promote forage crop productivity in the drought–suffering Salamiyya area, overpopulation, and water mismanagement in the agricultural field, the modified FAO– Aqua Crop 2012 program which can be used with other programs to simulate the recommended strategies to select the best one for cultivating alfalfa, barley, and vetch, compared with the area’s farmer practices (control). The results showed the importance of the application of mathematical modeling to cope with the climate of the area, cultivation date, and land suitability for each crop from the method of irrigation scheduling. The results of the statistical analysis proved that there are significant differences between the number of days even the date of cutting, Branches number per plant, Plant’s height, and yield at (5%) level. Furthermore, the agricultural water productivity would be increased by 63%, 45%, and more than 120% compared to the traditional field application for barley, vetch, and alfalfa, respectively. The program confirmed that the sprinkler irrigation method is the best in terms of (WUE) and suitability to environmental and economic conditions. Employing the virtual water concept and changing the alfalfa cultivated area to barley or vetch, we can get a profit of 898,42 /ha, saving 0.4–0.6 MCM/30–45 ha per year. Consequently, going ahead of the context of achieving sustainable development in this area. Finally, the integrated program AquaCrop and other programs can be considered modern and sophisticated tools to save water and costs in addition to obtaining very accurate results.